The development of patient oriented strategy to enhance medication adherence: the pharmaceutical perspective - Huang, Fu De (2017)
Non-adherence to medical treatment is the current worldwide problem that may result in the poor treatment result and unnecessary medical system expenditure. In essence, numerous medication adherence interventions have been designed and proved to improve the adherence efficiently. However, rare articles focus on the combination of these current interventions and the strategic planning from the business perspective. On the other hand, the pharmaceutical companies have been criticized for their profit-oriented strategy. The firms are facing the contradiction between profitability and cooperate social responsibility. Therefore, it forces them to change their promotional strategy from profit-oriented planning to patient-oriented planning. This dissertation aims to provide the pharmaceutical managers the flowchart for patient oriented planning that takes into account of both the patient related factors and business operational factors.